2016
DOI: 10.1242/jeb.142729
|View full text |Cite
|
Sign up to set email alerts
|

Improved cardiac filling facilitates the postprandial elevation of stroke volume inPython regius

Abstract: To accommodate the pronounced metabolic response to digestion, pythons increase heart rate and elevate stroke volume, where the latter has been ascribed to a massive and fast cardiac hypertrophy. However, numerous recent studies show that heart mass rarely increases, even upon ingestion of large meals, and we therefore explored the possibility that a rise in mean circulatory filling pressure (MCFP) serves to elevate venous pressure and cardiac filling during digestion. To this end, we measured blood flows and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…It has been suggested that specific arterial composition and microstructure confer the mechanical properties that enable arteries of different vertebrates to perform similarly at their normal in vivo pressures (Gibbons and Shadwick, 1989;Shadwick, 1999). The snake vascular system experiences further mechanical stress during the postprandial period as a result of the concomitant rise in both heart rate and stroke volume (Secor et al, 2000;Secor and White, 2010;Zerbe et al, 2011;Enok et al, 2016). These adjustments are necessary to match the severalfold increase in metabolism over the course of numerous days following ingestion of large meals (Andrade et al, 1997;Andersen et al, 2005;Gavira and Andrade, 2013) along with the concomitant tissue growth (Secor and Diamond, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that specific arterial composition and microstructure confer the mechanical properties that enable arteries of different vertebrates to perform similarly at their normal in vivo pressures (Gibbons and Shadwick, 1989;Shadwick, 1999). The snake vascular system experiences further mechanical stress during the postprandial period as a result of the concomitant rise in both heart rate and stroke volume (Secor et al, 2000;Secor and White, 2010;Zerbe et al, 2011;Enok et al, 2016). These adjustments are necessary to match the severalfold increase in metabolism over the course of numerous days following ingestion of large meals (Andrade et al, 1997;Andersen et al, 2005;Gavira and Andrade, 2013) along with the concomitant tissue growth (Secor and Diamond, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For reptiles, feeding elicits marked elevations in oxygen consumption rate ( _ V O 2 ) that last for several hours (Secor and Diamond, 1999;Hicks et al, 2000;Wang et al, 2001a;Overgaard et al, 2002a;Hicks and Bennett, 2004;Enok et al, 2013;Wearing et al, 2016). This postprandial increase in oxygen demand necessitates increased _ Q to sufficiently supply tissues with oxygen Secor et al, 2000;Wang et al, 2001a;Hicks and Bennett, 2004;Andersen et al, 2005;Secor and White, 2010;Enok et al, 2012Enok et al, , 2013Enok et al, , 2016Wearing et al, 2016). In terrestrial vertebrates, _ Q can be modulated by changes in heart rate ( f H ) and/or V S .…”
Section: Introductionmentioning
confidence: 99%
“…Sandblom et al, 2005;Skals et al, 2005Skals et al, , 2006Enok et al, 2016). By mobilizing blood from the veins, preload pressure may be maintained, or even increased, despite the increased heart rate during activity (Sandblom et al, 2005;Skals et al, 2006).…”
Section: Introductionmentioning
confidence: 99%